2020
DOI: 10.1155/2020/9205197
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Reveals Pathogenicity-Related Loci in Shewanella algae

Abstract: Shewanella algae is an emerging marine zoonotic pathogen and accounts for considerable mortality and morbidity in compromised hosts. However, there is scarce literature related to the understanding of the genetic background of virulence determinants in S. algae. In this study, we aim to determine the occurrence of common virulence genes in S. algae using whole-genome sequence and comparative genomic analysis. Comparative genomics reveals putative-virulence genes related to bile resistance, chemotaxis, hemolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In order to confirm whether they are key pathogenicity factors in S. algae, further studies should be conducted. In addition, we found several other virulence genes encoded in this species, which were consistent with previous results (Wang et al, 2020;Zago et al, 2020). We also identified other potential candidate genes overrepresented in CG genomes, such as speCEG (spermidine synthesis), potE (putrescine transport) (Fang et al, 2017;Guerra et al, 2018), cobS (cobalamin biosynthesis) or genes related to oxidative stress response, specifically the peroxidase encoding gen katG.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In order to confirm whether they are key pathogenicity factors in S. algae, further studies should be conducted. In addition, we found several other virulence genes encoded in this species, which were consistent with previous results (Wang et al, 2020;Zago et al, 2020). We also identified other potential candidate genes overrepresented in CG genomes, such as speCEG (spermidine synthesis), potE (putrescine transport) (Fang et al, 2017;Guerra et al, 2018), cobS (cobalamin biosynthesis) or genes related to oxidative stress response, specifically the peroxidase encoding gen katG.…”
Section: Discussionsupporting
confidence: 90%
“…isolated from clinical samples (Ramírez et al, 2010;Di Noto et al, 2016;Almuzara et al, 2017). Few studies are limited and focused on the analysis of the accessory genome of Shewanella spp., particularly on the mobilome, resistome, and virulome of S. algae isolates (Deng et al, 2019;Wang et al, 2020;Huang et al, 2022), which encode beneficial genetic traits that contribute to its survival. Recently, Zhong et al (2018) suggested that Shewanella spp.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, multi-omics data contribute to explore biological processes from a variety of perspectives [ 13 ], including genomics [ 14 ], transcriptomics [ 15 ], metabolomics [ 16 ], microbiomics [ 17 ], and proteomics [ 18 ]. The effects of drugs on macaques have been explored using multi-omics analysis, greatly promoting biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…including genomics [13], transcriptomics [14], metabolomics [15], microbiomics [16], and proteomics [17]. The effects of drugs on macaques have been explored using multi-omics analysis, greatly promoting biomedical research.…”
Section: Introductionmentioning
confidence: 99%